Grain yield and its components stability of bread wheat genotypes under rainfed conductions - Al-falahi, Muhammed Ali; Sadalla, Hussain Ahmed; Hussain, Shwana Ahmad (Sulaimani Journal for Pure and Applied Sciences, 2018)
Ten bread wheat genotypes (Saraa-1, Sham-4, Maxipak,Babaga-3, Jawhir-3, Sale, NS732, REGAA6-1, QAF2AA-3 and IPA-95) were sown during 2015-2016 growing season at three locations (Sulaimani, Erbil and Duhok) under two sowing dates (1 November and 1 December). Randomized Complete Block Design was used with three replications to estimate the stability of these genotypes. Three stability parameters (variance across environments, regression coefficient Bi and variance of deviation from regression Sdi) were used to identify the stability in yield and its components .The results showed that the genotypes Babaga-3 and Jawhir-3 had the best values according to stability parameters, indicating their wide adaptability over different environments and be considered as favored wheat genotypes under variable rainfall conditions in Iraq. The other genotypes gave a high stability, performance not superior in yield and other traits, as other superior traits could be introduced to other genotypes in the improvement breeding program.
Keywords: Bread wheat; yield components; stability genotype environment interaction regression